Promiscuous copulation attempts and discriminate pairing displays in male barn swallows as revealed by model presentation. Issue 2 (2nd April 2016) - Hasegawa, M.; Watanabe, M.; Nakamura, M.
Abstract : The current knowledge of male mate preferences based on female ornamentation is quite limited. Few experimental studies have been conducted; therefore, even basic information, such as male mate preferences for copulation and pairing, is lacking. Here we studied male mate preferences in Japanese barn swallows Hirundo rustica gutturalis, a socially monogamous passerine with biparental care, using a model presentation experiment. We presented each unmated male with a control female model that had typical whitish ventral feathers of this subspecies or with a chestnut model that had chestnut ventral feathers, which are found in other subspecies such as H. r. erythrogaster, and compared male behaviour towards these models. The number of male copulation attempts did not significantly differ between treatments. In contrast, the number of male pairing displays was significantly different between treatments: males courted less often towards a chestnut model than towards a control model. These results demonstrate indiscriminate copulation attempts but discriminate pairing displays in male swallows, which is consistent with Trivers' classic theory. We discuss the causes and consequences of the observed patterns.